The Strategic Role of DSN-MUI in Developing Islamic Economic Law - Handayani, Nur Sillaturohmah; Apriantoro, Muhamad Subhi; Al-Husnayaini, Malikah (University of Darusssalam Gontor, 2023)
••• English ••• This research aims to demonstrate the various strategic roles that can be implemented by DSN-MUI in developing Islamic economic law. The research method used is a descriptive qualitative analysis of written references, such as jurisprudence books, journals, and documents (also known as literature studies or literature research). The results showed that DSN-MUI has a strategic role as a supervisor, advisor, catalyst, supporter, marketer, and player in developing Islamic economic law in Indonesia theoretically-normatively and practically-applicatively. The role of DSN-MUI is very strategic to support and develop Islamic economic law in Indonesia to fulfill the public's need for legal fatwa’s for economic activities in product innovation that continues to develop in global competition. DSN-MUI fatwa’s are a reference and guideline for Islamic financial institutions, Islamic tourism, Islamic hospitals, and other Islamic industries to carry out economic activities with appropriate Islamic principles and Islamic law regulations. BI, as a national institution with authority in the banking sector, has given legitimacy to the DSN-MUI and its legal products. The committee oversees Islamic banks, LKS, insurance, venture capital, mutual funds, and others. In Indonesia, DSN-MUI catalyzes economic development and the Islamic financial industry, returning society to its original, especially in trade, investment, agriculture, and other economic activities following Islamic law regulations. ••• Indonesian ••• Penelitian ini bertujuan untuk menunjukkan berbagai peran strategis yang dapat dilakukan oleh DSN-MUI dalam mengembangkan hukum ekonomi syariah. Metode penelitian yang digunakan adalah analisis kualitatif deskriptif terhadap referensi tertulis, seperti buku-buku fiqh, jurnal, dan dokumen (disebut juga studi literatur atau penelitian kepustakaan). Hasil penelitian menunjukkan bahwa DSN-MUI memiliki peran strategis sebagai pengawas, penasihat, katalisator, pendukung, pemasar, dan pemain dalam mengembangkan hukum ekonomi syariah di Indonesia secara teoritis-normatif dan praktis-aplikatif. Peran DSN-MUI sangat strategis untuk mendukung dan mengembangkan hukum ekonomi syariah di Indonesia untuk memenuhi kebutuhan masyarakat akan fatwa hukum kegiatan ekonomi dalam inovasi produk yang terus berkembang dalam persaingan global. Fatwa DSN-MUI menjadi acuan dan pedoman bagi lembaga keuangan syariah, pariwisata syariah, rumah sakit syariah, dan industri syariah lainnya untuk menjalankan kegiatan ekonomi dengan prinsip syariah yang sesuai dan aturan hukum Islam. BI, sebuah lembaga nasional yang memiliki otoritas di bidang perbankan, telah memberikan legitimasi terhadap DSN-MUI dan produk hukumnya. Komite tersebut membawahi bank syariah, LKS, asuransi, modal ventura, reksadana, dan lain-lain. Di Indonesia, DSN-MUI mengkatalisasi perkembangan ekonomi dan industri keuangan syariah, mengembalikan masyarakat ke kondisi semula, terutama dalam perdagangan, investasi, pertanian, dan kegiatan ekonomi lainnya sesuai dengan aturan hukum Islam.